Engaging communities through participatory learning action for the control and prevention of diabetes: A protocol for the Process Evaluation of the EMPOWER-D trial in Pakistan and Afghanistan - Maria Ishaq Khattak; Khalid Rehman; Saima Afaq; Sabeen Saeed Butt; Gul Ghutai; Refat Hanifi; Murtaza Hofiani; Amber Tahir; Rubia Zafar; Hannah Maria Jennings (PLoS ONE, 2026)
Background Type 2 diabetes is a growing challenge in low- and middle-income countries (LMIC), where health systems face major capacity gaps. Participatory learning and action (PLA) has shown effectiveness in preventing type 2 diabetes in Bangladesh, but little is known about its use in other LMICs for diabetes. The EMPOWER-D (Engagement of community through Participatory learning and action for cOntrol and prevention of type 2 diabetes) trial is testing PLA for diabetes prevention in communities in Pakistan and Afghanistan. This protocol describes the plans for the embedded process evaluation (PE). Methods The PE will use a mixed-methods design across three sites, following the UK Medical Research Council framework for PE, examining implementation, mechanisms of impact and context. Implementation will be assessed using adaptation reports, fidelity checklists, attendance data and supervisor reports. Mechanisms of impact will be explored through interviews, focus group discussions and photovoice. Contextual factors will be examined through interviews with participants, community mobilisers, supervisors and key stakeholders. Quantitative data will be analysed descriptively, while qualitative data will undergo thematic analysis using a theory of change framework. Comparative analysis will identify common and context-specific influences. Discussion This is the first multi-country PE of a PLA intervention for diabetes prevention to our knowledge, and the first in Afghanistan and Pakistan. The study will provide insights into how the intervention was delivered, how and why it worked (or did not work) and the contextual factors shaping outcomes. Findings will inform the adaptation and scale-up of participatory approaches for non-communicable disease prevention in resource strained setting health systems. Trial registration: ClinicalTrials.gov: NCT06561126 (registered 23 August 2024); NCT06570057 (registered 26 August 2024).